Impact of pre-existing fabrics and multi-phase oblique extension on Cenozoic fault patterns, Wichianburi sub-basin of the Phetchabun rift, Thailand. (January 2019) - Pongwapee, Sopon; Morley, Christopher K.; Won-in, Krit
Abstract: Cenozoic fault patterns associated with rift development in the Wichianburi Sub-Basin show a wide range of controls at different scales including influence by the margin of a Permian basin, and NW-SE to NE-SW trending Triassic folds and faults. During the Late Oligocene-Early Miocene phase 1 normal faults (NNW-SSE to NNE-SSW trends) developed in response to ∼ E-W extension. Faults predominantly trend NNW-SSE to N-S during this phase. During the Middle Miocene-Pliocene the extension direction rotated to a more NW-SE orientation. The old fault orientations were reactivated, and new faults also developed with predominantly NNE-SSW to NE-SW orientations. Many new faults nucleated within the syn-rift section and were not directly influenced by pre-existing fabrics in the pre-rift section. Four types of phase 2 fault can be identified: Type 1 = newly formed faults that strike sub-orthogonal to the phase 2 extension direction, Type 2 = newly formed faults that strike between the phase 1 fault orientations and Type 1 faults. Type 3 = newly formed faults that strike at angles greater than 90° with respect to the phase 2 extension direction. Type 4 = reactivated phase 1 faults. Local stress rotations, and fault linkage rotations explain many of the Type 2 and 3 fault orientations. The stress rotation in the Middle Miocene is observed in other basins in Central Thailand, notably the Suphan Buri and Phitsanulok Basins, where a range of fault patterns are produced by the effects of inherited fabrics plus multi-phase rifting. Highlights: Curved fault splays related to multi-phase oblique extension. Linkage along first phase fault trends by second phase faults. Regional change from E-W to NW-SE extension in Middle Miocene. Variety of orientations to second phase faults similar to results from analogue models.